Psychological well-being of personality - Алещенко, Віктор (Київський національний університет імені Тараса Шевченка, 2024)
Background. The relevance of the study of the psychological well-being of an individual is due to the need to clarify the content, characteristics and criteria of this phenomenon, as well as to identify a functional model of the psychological well-being of an individual based on the theoretical analysis of the works of scientists and own research. The purpose of the article is to determine the essence, structure and factors of a person's psychological well-being. To find out the nature of the phenomenon of psychological well-being; describe the main criteria of psychological well-being; analyze the characteristics of psychological well-being.Methods. To achieve the goal, such scientific methods were used as: analysis, comparison, substantiation, generalization, systematization of theoretical and practical material on psychological well-being.Results. Considered examines the phenomenon of psychological well-being of an individual as an integrative formation, which manifests itself in the degree of focus on the fulfillment of the main components of positive human functioning, subjectively perceived as satisfaction withoneself and one's life. It has been established that the psychological well-being of an individual is related to his or her value orientations (life goals, life processes, and life efficiency) and vitality. It is shown that psychological well-being is the result of a sense of achievement and success inprofessional activities, harmony in personal life and attitude towards people.Сonclusions. Psychological well-being and its components help to understand the role of mental health (if we consider health as a component of well-being), its conditions and factors (if we consider a healthy personality) as a mature, authentic and successful self-actualized person in various areas. Psychological well-being is an indicator of a person's state of health, his social and psychological adaptability and efficiency of functioning.

Вступ . Актуальність дослідження психологічного благополуччя особистості зумовлена необхідністю на основі теоретичного аналізу праць науковців і власних досліджень уточнити зміст, характеристики та критерії цього феномена, а також виокремити функціональну модель психологічного благополуччя особистості. Мета статті полягає у визначенні сутності, структури та чинників психологічного благополуччя людини. З'ясувати природу феномена психологічного благополуччя; описати основні критерії психологічного благополуччя; проаналізувати характеристики психологічного благополуччя.Методи . Для досягнення поставленої мети були використані такі наукові методи, як: аналіз, порівняння, обґрунтування, узагальнення, систематизація теоретичного та практичного матеріалу щодо психологічного благополуччя.Результати . Розглянуто феномен психологічного благополуччя особистості як інтегративного утворення, що проявляється ступенем досягнення основних складових позитивного функціонування людини і суб'єктивно сприймається як задоволеність собою та своїм життям. Встановлено, що психологічне благополуччя особистості пов'язане з її ціннісними орієнтаціями (життєвими цілями, життєвими процесами й ефективністю життя) та життєстійкістю. Показано, що психологічне благополуччя є відображенням відчуттів досягнення успіху у професійній діяльності, гармонії в особистому житті і ставленні до людей.Висновки . Психологічне благополуччя та його складові допомагають зрозуміти роль психічного здоров'я (якщо розглядати здоров'я як складову благополуччя), його умови та чинники (якщо розглядати здорову особистість) як зрілої, автентичної та успішної самоактуалізованої людини в різних сферах. Психологічне благополуччя – це показник стану здоров'я людини, її соціально-психологічної адаптованості та ефективності функціонування.
Психологічне благополуччя особистості
Keywords: психологічне благополуччя; внутрішні ресурси; особистість; особистісний потенціал; ставлення до людей; psychological well-being; internal resources; personality; personal potential; attitude towards people